An efficient two‐party authentication key exchange protocol for mobile environment. (28th May 2017) - Qi, Mingping; Chen, Jianhua
Summary: The primary goal of this research is to ensure secure communications by client‐server architectures in mobile environment. Although various two‐party authentication key exchange protocols are proposed and claimed to be resistant to a variety of attacks, studies have shown that various loopholes exist in these protocols. What's more, many two‐party authentication key exchange protocols use timestamp to prevent the replay attack and transmit the user's identity in plaintext form. Obviously, these methods will lead to the clock synchronization problem and user's anonymity problem. Fortunately, the three‐way challenged‐response handshake technique and masking user's original identity with a secret hash value used in our study address these problems well. Of course, the proposed protocol based on elliptic curve cryptography supports flawless mutual authentication of participants, agreement of session key, impersonation attack resistance, replay attack resistance, and prefect forward secrecy, as well. The analyses in the aspects of efficiency and security show that the proposed protocol is a better choice for mobile users. Abstract : To ensure secure communications by client‐server architectures in mobile environment, a new two‐party authentication key exchange protocol based on elliptic curve cryptography is proposed. The proposed protocol uses the three‐way challenged‐response handshake technique to overcome the clock synchronization problem and protects user's anonymity well by masking user's original identity with a secret hash value.